Atividade antioxidante in vitro do extrato etanólico das folhas de Luehea divaricata Mart. - Arantes, Leticia Priscilla (2012)
Oxidative stress has been linked to some neurodegenerative disorders. Current therapies are limited to attenuate the symptoms, however some studies have shown that antioxidant compounds may be able to prevent or delay neuronal oxidative damage, including those present in plant extracts. For these reasons, this study investigated the possible antioxidant activity of the ethanolic extract of Luehea divaricata leaves in brain of rats in vitro and the possible antioxidant mechanisms involved. The extract was evaluated against basal and sodium nitroprusside (SNP) 5 μM induced lipid peroxidation in brain of rats through measurements of thiobarbituric acid reactive substances (TBARS) production. Slices of brain areas were treated with SNP 100 M and extract to determine cellular viability by MTT reduction assay. Scavenger activity was evaluated against NO, DPPH and OH through Griess reagent, DPPH and deoxyribose oxidation assays, respectively. The chelating and reducing capacity for iron were determined by the orto-phenantroline method. The extract was screened by HPLC for the presence of gallic, chlorogenic, and caffeic acids, quercetin, rutin, and kaempferol. Only rutin was detected and then was used, in the same concentrations of the extract, as standard in all assays. L. divaricata extract (1-10 μg/ml) protected against induced lipid peroxidation, decreased basal levels of TBARS (about 50%) and maintained the cells viable. The extract was not able to protect deoxyribose against OH and to chelate iron, however it inhibited NO and DPPH in 33.14% at 20 μg/ml and 53.93% at 50 μg/ml respectively, and showed a reducing power in a concentration and time dependent manner. Therefore, L. divaricata ethanolic leaf extract showed antioxidant properties in vitro at low concentrations. The antioxidant mechanisms were related to scavenger activity on reactive oxygen and nitrogen species and metal reducing property. These effects were similar or more powerful than rutin in same concentrations in all assays, except in NO scavenger activity, and, thus, other unidentified compounds present in the extract appear to be associated with the effects observed in this study. More studies are needed regarding the identification of these compounds and the neuroprotective activity of the extract.